Factor V Has Anticoagulant Activity in Plasma in the Presence of TFPIα: Difference between FV1 and FV2 - van Doorn, Peter; Rosing, Jan; Duckers, Connie; Hackeng, Tilman M.; Simioni, Paolo; Castoldi, Elisabetta (Thrombosis and Haemostasis, 2018)
Background Activated factor V (FVa) is a potent procoagulant cofactor in the prothrombinase complex, whereas its precursor factor V (FV) stimulates the inhibition of factor Xa (FXa) by tissue factor pathway inhibitor-α (TFPIα), presumably by promoting TFPIα binding to phospholipids. Plasma FV comprises two glycosylation isoforms (FV1 and FV2) with low and high phospholipid-binding affinity, respectively. The FV1/FV2 ratio is increased in carriers of the FV R2 haplotype.Objective This article demonstrates the TFPIα-cofactor function of FV in plasma and compares FV1 and FV2.Materials and Methods Thrombin generation at low TF concentration was measured in FV-depleted plasma reconstituted with 0 to 100% FV, FV1 or FV2, and in 122 individuals genotyped for the R2 haplotype. The TFPIα-cofactor activities of FV1 and FV2 were also investigated in a model system of TFPIα-mediated FXa inhibition.Results In the FV titration, thrombin generation first increased (up to 5% FV) and then progressively decreased at higher FV concentrations. This anticoagulant effect of FV, which was also observed with FV2 but not with FV1, was largely abolished by anti-TFPIα antibodies, suggesting that it reflects TFPIα-cofactor activity of FV. In the model system of TFPIα-mediated FXa inhibition, FV2 was a more potent TFPIα-cofactor than FV1, in line with their respective phospholipid affinities. Accordingly, FV R2 carriers had higher thrombin generation than non-carriers, even after correction for demographics and plasma levels of coagulation factors and inhibitors.Conclusion FV (and particularly its FV2 isoform) contributes to the TFPIα-dependent down-regulation of thrombin generation in plasma triggered with low TF.
Keywords: factor V; tissue factor pathway inhibitor; R2 haplotype; thrombin generation; phospholipids